Analisis Kemampuan Pemecahan Masalah Materi Pecahan ditinjau dari Gaya Kognitif Field Dependent-Field Independent Siswa SMP - Derel Filandy Kaunang; Noper Pamula; James U.L. Mangobi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to describe the problem solving ability of the field dependent - field independent cognitive style of junior high school students. The kind of this research is descriptive with qualitative methods. Participants in this study were grade VII students of SMP Negeri 3 Tondano who represented each cognitive style of 6 students, namely field dependent and field independent cognitive styles. The research subjects used a purpose sampling technique. The data analysis technique used is data presentation, data simplification and conclusion drawing. The results of this study are field dependent subjects can understand the problem which determines or written down but not exactly what is known and asked from the problem, then plans problem solving but often leads to inappropriate solutions, in carrying out problem solving, field dependent subjects often do not carry out solving problems systematically so that the results obtained are not appropriate and in re-examining the field dependent subjects tend not to re-examine the solutions made because they experience problems in planning and implementing problem solving. Subject field - independent in understanding the problem can know what is known and asked, in planning problem solving, able to develop a plan of completion well. Then in carrying out problem solving, having the ability to carry out the calculation process correctly but in re-examining the field independent subject often ignores this. Keywords: Field Dependent, Field Independent, Cognitive Style, Problem Solving.